HUBUNGAN TINGKAT PENGETAHUAN REMAJA PUTRI DENGAN PERILAKU PENANGANAN DISMENORE PRIMER - Dea Riskha Fitriliana (Journal of Midwifery and Health Administration Research, 2023)
Background: Indonesian women who experience primary dysmenorrhoea overcome it more by consuming painkillers on the market. Behavior based on knowledge will be more lasting than behavior that is not based on knowledge. The purpose of this study was to determine the relationship between the level of knowledge of adolescent girls about primary dysmenorrhoea with the behavior of handling primary dysmenorrhoea in SMP N 1 Bulakamba, Bulakamba District, Brebes Regency. Method: This type of research is an analytical survey with a cross sectional design and the number of samples is 58 adolescent girls, with the respondents of the study being grade IX students of SMP N 1 Bulakamba. Purposive sampling technique. Data on knowledge and handling behavior of adolescent girls in overcoming primary dysmenorrhoea were collected using questionnaires. Data analysis with univariate and bivariate analysis using Chi Square test. Results: The results of the study were that adolescent girls' knowledge about primary dysmenorrhoea was 29.3% with good categories, and 70.7% less. As many as 74.1% of adolescent girls do primary dysmenorrhoea. The results of the statistical test using the fisher exact test obtained a p value of 0.045 <0.05. Conclusion: there is a relationship between the level of knowledge of adolescent girls about primary dysmenorrhoea and the behavior of handling primary dysmenorrhoea. It is hoped that health workers can provide health education about dysmenorrhea so that it can increase awareness of women's reproductive health, especially related to handling dysmenorrhoea.